Informacinės technologijos matematikai vizualizuoti ir tyrinėti - Dagienė, Valentina; Jasutienė, Eglė (Information & Media, 2007)
Straipsnyje aptariama matematikos mokymo naudojant informacines technologijas problematika. Kompiuteris suteikia besimokančiajam tyrinėjimo, modeliavimo, konstravimo erdvę – matematikos mokymosi mikropasaulius. Tam reikia parengti kompiuterinių priemonių, tinkančių matematikai mokytis konstruktyvistiniu metodu. Prieš keletą metų Lietuvos mokyklos aprūpintos lokalizuota mokomąja kompiuterine programa „Dinaminė geometrija“ (originalus pavadinimas „Geometer’s Sketchpad“). Straipsnyje nagrinėjama šios programos naudojimo matematikos pamokose problematika, programos savybės ir ypatumai, aptariami dinaminių brėžinių konstravimo ir programos galimybių išplėtimo būdai. Analizuojama dinaminių brėžinių komplekto pagrindinės mokyklos matematikos kursui mokyti rengimo problematika, pateikiamas dinaminio brėžinio konstravimo pavyzdys. Visualization and exploring mathematics using information technologies Valentina Dagienė, Eglė Jasutienė Summary A five-year long research has been developed in two phases. The first phase was to analyze problematic dimensions of teaching mathematics in schools using computer-based technologies and searching for the most suitable software for the National curriculum of mathematics. The next step was to investigate (also to localize) the “Geometer’s Sketchpad” and to built various sets of dynamic sketches for teaching and learning mathematics in basic schools. More than 900 dynamic sketches have been developed within 9th and 10th grades (years 16 and 17) mathematics curriculum. The construction of dynamic sketches shows that it is difficult for teachers of mathematics to construct these sketches. It is not enough to know mathematics but teacher need deeper sophistication in this software. The principle of the “Geometer’s Sketchpad” is rather simple: we have an empty sheet of paper, ruler, pencil, calculator, and several drawing commands, all you need to create. Very often quite complex dynamic images have to be created by using the merest means. In such case just a few steps have to be performed. For example, to create a decision model of inequality the algorithm of approx. 200 has to be implemented. “Geometer’s Sketchpad” does not limit the possible number of algorithm steps. It rather depends on the computer facilities as well as a person’s invention. Therefore, some problems of construction of dynamic sketches was found and presented in this paper.